Rb-Sr AND K-Ar WHOLE ROCK AGES OF THE PLUTONIC BODIES FROM THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - タカハシ, ユウヘイ; アラカワ, ヨウジ; サキヤマ, トオル; オサナイ, ヤスヒト; マキモト, ヒロシ; TAKAHASHI, Yuhei; ARAKAWA, Yoji; SAKIYAMA, Tohru; OSANAI, Yasuhito; MAKIMOTO, Hiroshi (National Institute of Polar Research, 1990)
P(論文) Rb-Sr whole rock isochron ages were determined on the two plutonic bodies from the Sør Rondane Mountains. Tonalite of the Nils Larsen Group (Nils Larsen Tonalite), being one of the representative older type intrusive rocks, gave an age of 956±39 Ma with an initial ^<87>Sr/^<86>Sr ratio of 0.7024. The other is the Lunckeryggen Granite, which is the most representative granite of younger type, gave an age of 525±32 Ma with an initial ^<87>Sr/^<86>Sr ratio of 0.7050. Two whole rock K-Ar ages on this granite were 406±20 and 415±21 Ma. It appears from the above that tonalitic magma has been intruded in Late Precambrian and that granitic magma in Early Paleozoic. Another thermal event occurred in Middle Paleozoic. Difference of initial Sr isotopic ratios between the Nils Larsen Tonalite and the Lunckeryggen Granite may reflect the crustal development in this area. departmental bulletin paper